Pro-social activities and grassroots initiatives during Russia's attack on Ukraine - institutional field in aid activities for Ukraine (the case of the "Wroclaw Railway Station" - Perchla-Włosik Aleksandra M. (2022)
The aim of the article is to determine whether the formation of organisational structures appears in the transformation of grassroots initiatives "coming from the people", in the course of activities for refugees from Ukraine. How to relate the theory of the organisational field to them and what are the possible consequences of institutionalising these endeavours.